Pengaruh Service Quality dan Brand Trust Terhadap Customer Satisfaction Listrik Prabayar pada Pelanggan PT PLN (Persero) ULP Mojoagung - Eka Lintang Putri; Yosi Afandi (Indo Publishing, 2026)
Customer Satisfaction is a key factor in maintaining customer loyalty, particularly in prepaid electricity services provided by PT PLN (Persero) ULP Mojoagung, where satisfaction is shaped by Service Quality and Brand Trust. This study analyzed the partial and simultaneous effects of Service Quality and Brand Trust on Customer Satisfaction among prepaid electricity customers. A quantitative explanatory approach was applied to 100 respondents selected through purposive sampling from a population of 53,506 customers, determined using Slovin's formula. Data were collected via questionnaires and analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination in SPSS 25. Results showed that Service Quality (t = 6.672 > 1.985) and Brand Trust (t = 7.321 > 1.985) each had a positive and significant partial effect on Customer Satisfaction, while both variables simultaneously influenced Customer Satisfaction by 89.9% (Adjusted R² = 0.899). These findings indicate that improving Service Quality and strengthening Brand Trust are essential for sustaining Customer Satisfaction